Serum 25-hydroxyvitamin D is associated with stroke history in a reverse J-shape - Pan, Jue-heng; Wu, Shuo-long; Ma, Jing-xiang; Chang, Long; Zheng, Ying-feng; Wang, Xiao-dong (Frontiers in Neurology, 2023)
25-hydroxyvitamin D (25(OH)D), the major form of vitamin D in the body, has a nonlinear association with stroke risk. However, the association is not fully understood. The specific shape of the association and the ideal value of 25(OH)D related to minimum risk of stroke remain unclear. We conducted the study aiming to establish the correlation between circulating 25(OH)D and stroke risk, and determine the ideal value of 25(OH)D in related to the minimum stroke risk. Data from the National Health and Nutrition Examination Survey (NHANES) were used for analyses. We used multivariate logistic regression analysis with fitted smooth curves to explore the relationship between 25(OH)D and stroke risk. Subsequently, 40,632 participants in all were enrolled in the study. Using multivariate logistic regression analysis with fitted smooth curves, a J-shaped association between 25(OH)D and stroke risk was determined, where the minimum stroke risk for the 25(OH)D level was about 60 nmol/L. Compared with the third quintile (53.2–65.4nmol/L) of 25(OH)D, risk of stroke showed an increasing trend below and above the reference range of 25(OH)D, a 47%(OR 1.47,95%CI 1.18–1.82) increased risk of stroke in the lowest level group (≤39.3 nmol/L). Using data from a large, cross-sectional cohort program, we found that circulating 25(OH)D was related to stroke risk in a J-shaped manner. Given how the causal relationship between circulating 25(OH)D and risk of stroke has not been established, more high-quality evidence based on the J-shaped feature is needed to elucidate the link between vitamin D and stroke risk, and the effect of vitamin D supplements on stroke prevention.